High‐Temperature Ternary Oxide Phases in Tantalum/Niobium–Alumina Composite Materials. Issue 8 (14th May 2022) - Eusterholz, Michael K.; Boll, Torben; Gebauer, Julian; Weidner, Anja; Kauffmann, Alexander; Franke, Peter; Seifert, Hans Jürgen; Biermann, Horst; Aneziris, Christos G.; Heilmaier, Martin
Abstract : Coarse‐grained composites of refractory ceramics and refractory metals are a novel approach for materials at application temperatures up to 1500 °C. Al2 O3 and the refractory metals Nb and Ta are suitable candidates for enhanced thermal shock capability, as they show similar thermal expansion. During fabrication, a key aspect to consider is the possible formation of additional phases upon interaction of the constituent phases as well as through reaction with the environment. X‐Ray diffraction (XRD) and investigations of the microstructure with scanning electron microscopy methods unveil Al2 O3 –Nb composite to form NbO, whereas for Al2 O3 –Ta the ternary compound aluminum tantalate (AlTaO4 ) is found. Thermodynamic calculations show that the changing oxygen solubility in Nb accounts for the formation of NbO, and explain the absence of a corresponding niobate (AlNbO4 ) phase. AlTaO4 is identified as the disordered tetragonal high‐temperature modification. Abstract : Fabrication of refractory ceramic ‐ refractory metal composites via sintering leads to the formation of refractory metal oxides. Thermodynamic calculations predict α‐Al2 O3 with Ta to form a ternary oxide (AlTaO4 ) and α‐Al2 O3 with Nb to form NbO. This is confirmed experimentally by diffraction methods.